METODOLOGI KAJIAN ISLAM: Studi Analisis Hukum Fiqh dalam Pendekatan Rasional Argumentatif (Metode Burhani) - Ahmad Khoirur Roziqi; Syamsun Ni’am (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2023)
The aim of this writing is to analyze fiqh law in a rational argumentative approach or what is often called the burhani method in Islamic studies. In writing this, the author searched for and studied literature related to the object of this study, not only relying on books but in journals, magazines, and so on. Using a rational argumentative approach based on library data accompanied by discourse analysis, it was found that fiqh law can be produced using the burhani method, namely a method in Islamic studies that uses ratio/reason. This burhaniyah method developed in various forms of reasoning methods or ijtihad methods, both those with a deductive reasoning pattern (istinbathi) and those with an inductive reasoning pattern (istiqra'i).